Glycoprotein profiling of Staphylococcus epidermidis and its role in biofilm formation and antibiotic resistance / Nur Alia Othman - Othman, Nur Alia (2021)
Staphylococcus epidermidis is the most frequently detected coagulase-negative staphylococcus (CoNS) that is commonly responsible for catheter-related and central nervous system (CNS) infections. It is an opportunistic pathogen capable of forming biofilm which contributes to device-related infections and resistance to antibiotics. The ability to form biofilm has been linked with glycoproteins in biofilm-producing bacteria. This study investigates the differential glycoprotein expression between the biofilm producer and nonbiofilm producer of S. epidermidis and also its involvement in enhancing antibiotic resistance of the biofilm. S. epidermidis strains were subjected to N- and O-glycosylation inhibition followed by physical characterisation by Field Emission Electron Scanning Microscopy (FESEM) and antibiotic resistance profiling. The absence of O-glycosylation ascertains with reduced biofilm production of ATCC35984 strain and biofilm thickness. Subsequently, treatment with vancomycin, rifampicin and tetracycline showed that the antibiotics were more effective against O-glycan deficient biofilm. Differential protein expression was observed in planktonic and biofilm cultures of both biofilm and nonbiofilm producing strains. Glycoproteins were detected using Pro-Q® Emerald 300 Glycoprotein staining and subjected to mass spectrometry (LC-MS) identification. Out of the 17 spots characterized, 55 glycoproteins were identified for glycoprotein site prediction as well as protein interaction analysis using STRING tool and Clusters of Orthologous Genes (COGs). Majority of these proteins were found to carry either N- or O-glycosylation sites with some known to be related with biofilm formation such as glutamate synthase and influence antibiotic resistance for example glutamate-tRNA ligase. Therefore, O-glycans are suggested to have potential impact on biofilm formation and antibiotic resistance of S. epidermidis which warrants further evaluation and validation.